p23/Tmp21 Associates with Protein Kinase Cδ (PKCδ) and Modulates Its Apoptotic Function - Wang, HongBin (American Society for Biochemistry and Molecular Biology, 2011)
There is emerging evidence that C1 domains, motifs originally identified in PKC isozymes and responsible for binding of phorbol esters and diacylglycerol, interact with the Golgi/endoplasmic reticulum protein p23 (Tmp21). In this study, we investigated whether PKCδ, a kinase widely implicated in apoptosis and inhibition of cell cycle progression, associates with p23 and determined the potential functional implications of this interaction. Using a yeast two-hybrid approach, we found that the PKCδ C1b domain associates with p23 and identified two key residues (Asp(245) and Met(266)) implicated in this interaction. Interestingly, silencing p23 from LNCaP prostate cancer cells using RNAi markedly enhanced PKCδ-dependent apoptosis and activation of PKCδ downstream effectors ROCK and JNK by phorbol 12-myristate 13-acetate. Moreover, translocation of PKCδ to the plasma membrane by phorbol 12-myristate 13-acetate was enhanced in p23-depleted LNCaP cells. Notably, a PKCδ mutant that failed to interact with p23 triggered a strong apoptotic response when expressed in LNCaP cells. In summary, our data compellingly support the concept that C1 domains have dual roles both in lipid and protein associations and provide strong evidence that p23 acts as an anchoring protein that retains PKCδ at the perinuclear region, thus limiting the availability of this kinase for activation in response to stimuli.